(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This scientific article provides a comprehensive analysis of the substantive, methodological, and institutional transformation of social sciences and humanities in the context of a digital society, as well as the processes of interdisciplinary integration. It substantiates that under the influence of digital technologies, the research objects and subjects of social sciences are expanding, leading to the emergence of new scientific directions. Using the examples of sociology, philosophy, cultural studies, political science, and the education system, the article highlights the significance of interdisciplinary approaches. The research findings demonstrate the strategic role of social sciences and humanities in the development of a digital society.